Pemborosan Gaya Hidup Hangout dalam Perspektif Hadis - Wika Anjani; Mugiyono Mugiyono; Sulaiman M. Nur (Jurnal Penelitian Ilmu Ushuluddin, 2026)
The phenomenon of the hangout lifestyle among teenagers and university students reflects a shift from social interaction into a symbol of identity and social status, which potentially leads to consumptive behavior and wastefulness. This study aims to analyze the concept of wastefulness in Islam, particularly israf and tabzir from the perspective of hadith, and to examine wasteful practices within the hangout lifestyle. This research employs a qualitative method with a library research approach, using primary sources from authoritative hadith collections, along with hadith commentaries and contemporary literature, analyzed through thematic, contextual, and maqasid al-sharī‘ah approaches. The findings show that the Prophet’s hadith strictly prohibits all forms of wastefulness, both in the use of wealth and time. Isrāf refers to excess in permissible matters, while tabzir refers to the squandering of wealth without benefit. In the context of the hangout lifestyle, wastefulness occurs when such activities are carried out excessively and driven by hedonism and social image. Therefore, the Prophet’s hadith remains relevant as an ethical framework to guide a more proportional, beneficial, and value-oriented lifestyle in accordance with Islamic principles.